AKTUALISASI HUKUM ISLAM DI INDONESIA (Idealitas dan Realitas Hukum Pidana Islam) - Saidah, Saidah (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2013)
Islamic law as national law in Indonesia growing and developing normative values of islamic law has been applied to full conciousness by Islam society. Different from the judicial islamic law has not been any material including islamic criminal law is formulated through the legislative process in the form of legislation or other regulatory laws. The reality Indonesia is not law state or sekularism state, then fighting islamic with values integration approach seems more promising approach especially islamic crimanal law. Therefore, a serious effort is needed to exploreas much as possible and socialization of noble values embodied in islamic law.